Sábia no sábio é a atitude (Revista NUPEART, 2024)
The career of the artist, researcher and woman Ingrid Dormie Koudela is the subject of the reflections in this article. Fragments of memory related to the greatness of her work and her academic life are presented throughout the text. The importance of I.D.K.'s work in the artistic, cultural and educational training of children, young people and educators is highlighted, considering her pioneering role in discussions about theatre pedagogy in Brazil. More than fifty years dedicated to theatre and its imbrications with education are revisited.
Keywords: Theater; Theater pedagogy; Ingrid Dormien Koudela